An unequivocal good? Acknowledging the complexities of advance care planning. Issue 10 (October 2014) - Robins‐Browne, K.; Palmer, V.; Komesaroff, P.
Abstract Over the past few decades advance care planning (ACP) has become the subject of debate, research and legislation in many countries. Encouraging people to express their preference for treatment in advance, ideally in written form, seems a natural way to identify what someone might have wanted when they can no longer participate in decision‐making. The notion of ACP as an unequivocal good permeates much of the research and policy work in this area. For example, ACP is now actively encouraged in Australian federal and state government policies and the Victorian Government has recently published a practical ACP strategy for Victorian health services (2014–2018). However, advance care plan is ethically complex and the introduction of the Victorian health services strategy provides an opportunity to reflect on this complexity, particularly on the benefits and risks of ACP.